Spherical traveling wave hypothesis for geometric optical phase with speherical magnetic ferromagnetic system - İnç, Mustafa; Korpinar, Talat; Korpinar, Zeliha (Springer, 2023)
In this article, we investigate new constructions of optical Heisenberg spherical optical ferromagnetic spin of timelike magnetic fluids by de Sitter frame. Also, we approach spherical magnetic flows geometrically. Thus, we get total magnetic spherical phases of magnetic spherical timelike fluids. Finally, we construct new numerical presentations of optical spherical magnetic ferromagnetic particles by analytical spherical traveling wave interpretation.
Keywords: Spherical traveling wave hypothesis; Geometric phase; Optical fiber; Fluid equations; Heisenberg spherical ferromagnetic spin